Evaluacija valjanosti pre-braka Mean Corpuscular Volume value kao prediktivni test za status β-thalassemia - Almomani, Ali; Shraim, Ala'a; Atoom, Ali; Jehad, (Journal of Medical Biochemistry, 2022)
Background: The national mandatory premarital screening test is based on MCV > 80fL value for the detection of β-thalassemia to provide acceptance for marriage. The objective of this study is to assess the efficacy of MCV as a screening test for β-thalassemia trait in the present population. Methods: This study was conducted on 418 blood samples collected from adult individuals. The diagnosis of β‐thalassemia carrier was given to those having HbA2 values equal to or above 3.5%. The diagnostic reliability of different RBC indices and formulas in discriminating cases of β-thalassemia trait were evaluated. Finally, a new index called “Momani” was determined based on MCV, RDW and RBC count. Results:  β-thalassemia trait was identified in 10 % of the cases. The measured MCV value was significantly lower in β-thalassemia carrier group compared to non-carrier group (p =